Postharvest dehydration induces variable changes in the primary metabolism of grape berries - Conde, Artur (2018)
Postharvest dehydration causes changes in texture, color, taste and nutritional value of food due to the high temperatures and long drying times required. In grape berries, a gradual dehydration process is normally utilized for raisin production and for making special wines. Here we applied a raisin industry-mimicking dehydration process for eleven days at 50 °C to intact berry clusters from cv. Sémillon plants, and a set of molecular, cellular and biochemical analyses were performed to study the impact of postharvest dehydration in the primary metabolism. Transcriptional analyses by real time qPCR showed that several aquaporins (VvTIP1;2 and VvSIP1) and sugar transporters (VvHT1, VvSWEET11, VvSWEET15, VvTMT1, VvSUC12) genes were strongly upregulated. Moreover, the study of key enzymes of osmolytes metabolism, including mannitol dehydrogenase (VvMTD) and sorbitol dehydrogenase (VvSDH), at gene expression and protein activity level, together with the transcriptional analysis of the polyol transporter gene VvPLT1, showed an enhanced polyol biosynthesis capacity, which was supported by the detection of sorbitol in dehydrated grapes only. The metabolism of organic acids was also modulated, by the induction of transcriptional and biochemical activity modifications in malate dehydrogenases and malic enzymes that led to organic acid degradation, as demonstrated by HPLC analysis. Taken together, this study showed that primary metabolism of harvested berries was severely influenced in response to dehydration treatments towards lower organic acid and higher sorbitol concentrations, while sugar transporter and aquaporin genes were significantly upregulated.